Insomniacs after school. 3 - Ojiro, Makoto, 1982- (VIZ Media, LLC, 2023)
"Summer is swiftly approaching for sleepless high schoolers Nakami and Magari. Now members of their school's revived astronomy club, they're busy preparing for their first official club event, a meteor shower watch party! The city's annual fireworks festival is also coming up, and Nakami has promised to go with Magari. Every sleepless night brings the two closer, and their first high school summer promises to strengthen their bond even more..."--